2023
DOI: 10.1002/srin.202200791
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Based Direct Reduction of Iron Oxides Pellets Modeling

Abstract: The present study deals with the analyses of the direct reduction kinetics during the hydrogen reduction of industrial iron oxide pellets. Various types of pellets with different percentage of total iron content and metal oxides are examined. They are reduced at different temperatures and pressure (700–1100 °C and 1–6 bar) in hydrogen atmosphere. The reduction behavior is described in terms of time to reduction, rate of reduction, and kinetics constant. All the obtained results are analyzed through the employm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…It is well established that an increase of H 2 share in the reduction gas mixture leads to higher reduction rate of the iron oxides. [11,29,30] The same effect was reported for increases in temperature and partial pressure. [11,29] Higher porosity of the pellet improves the gas penetration into the unreacted core, and therefore it enhances reduction rate as well.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…It is well established that an increase of H 2 share in the reduction gas mixture leads to higher reduction rate of the iron oxides. [11,29,30] The same effect was reported for increases in temperature and partial pressure. [11,29] Higher porosity of the pellet improves the gas penetration into the unreacted core, and therefore it enhances reduction rate as well.…”
Section: Introductionsupporting
confidence: 72%
“…[11,29,30] The same effect was reported for increases in temperature and partial pressure. [11,29] Higher porosity of the pellet improves the gas penetration into the unreacted core, and therefore it enhances reduction rate as well. [11,31] Tortuosity is negatively affecting the reduction rate of the iron-ore pellet.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…In this view, it is easy to establish the real effect of hydrogen as a substitute for carbon monoxide in the direct reduction relating its usage to carbon consumption and carbon dioxide emissions reduction during ironmaking [17]. The hydrogen-based direct reduction process includes multiple types of chemical reactions, solid state, and defect-mediated diffusion (of oxygen and hydrogen species), several phase transformations, as well as massive volume shrinkage and mechanical stress buildup [18,19]. The volume expansion of the pellets is inevitable during the reduction, and the abnormal swelling would cause serious accidents, such as poor permeability, even collapse of the burden [20].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of some hard reducible phases such as fayalite and ferrites, sintering effects as well as α-γ Fe phase transformation (912 o C) are the most signifi cant factors affecting rate minimum phenomena 20 . It has been reported that the Polish Journal of Chemical Technology, 25,4,[81][82][83][84][85][86][87][88][89][90][91][92]10.2478/pjct-2023-0041 The reduction temperature has a great infl uence on the structure of the produced iron and its lattice strain [21][22] . By decreasing the reduction temperature, the pore structure becomes fi ner.…”
Section: Introductionmentioning
confidence: 99%